Al-Qur'an Berwajah Puisi Ala H.B. Jassin (Suatu Kajian Sejarah Tafsir di Indonesia) - Muh Daming K (Institut Agama Islam Negeri (IAIN) Kendari, 2009)
A masterpiece of H. B. Jassin at Al-Qur'an have Faced to Poem, differing from what is done/ conducted at in the middle of the 1970-an. In the form of translation poetic of Al-Qur’an called by is August Reading al-Qur’an, which done before all is to Form Translation of al-Qur’an in Indonesia become couplets as applying in poem methods by dot weigh against goal feel his language. Criticism to H. B. Jassin concerning matter read of al-Qur’an that is, reader placing x’self “outside al-Qur’an”, an reader which born from al-Qur’an. Feeling other read, reader grappling together, the reader which dialoguing, reader which follow moved in that circle; coil discourse. From here see there is people read to scream of al-Qur’an. Masterpiece of Jassin do not be accepted with either by most moslem scholars in Indonesia, opposing to the writing of him, goals of him to isn’t it the beauty of Jassinala al-Qur’an.